A better understanding of social-ecological systems is needed for adapting fisheries to climate change. (December 2020) - Salgueiro-Otero, Diego; Ojea, Elena
Abstract: Adaptation to climate change has traditionally been studied at the individual scale, with most studies focusing on specific adaptation actions and the potential of individuals to undergo such actions and reduce vulnerability to climate hazards. However, adaptation to climate change takes place at the broader scale of coupled social-ecological systems (SES), where decision making and adaptation policies are relevant. Despite the general need to understand adaptation in coupled systems, there is no evidence to date to the extent to which current adaptation and vulnerability studies are covering the full range of SES components. The present study contributes to this need by examining such coverage in applied studies of vulnerability, adaptation and SES sustainability in the field of small-scale fisheries. By means of a systematic review and comparison of case studies, we detected a gap between theory and implementation and a lack of consideration of several SES components in the adaptation and vulnerability literature. This gap is larger for the Interactions between social and ecological domains, and in the coverage of Related Ecosystems. By contrast, greater attention has been given to the Actors, Governance system and Resource unit components. On the basis of our findings, we propose a set of guidelines to better address adaptation in social-ecological systems by broadening the outlook of adaptation studies and policies, specifically by considering interactions, evaluating outcomes and integrating cultural and ecological variables. Highlights: Adaptation to climate change is a process that takes place at the social-ecological systems level. The diversity of cultural, social and human aspects have not been deeply explored under this framework. A broader ecological processes perspective is needed in order to cover the complexity of social-ecological systems. Little evidence exists on interactions and connectivity among social-ecological dimensions and scales.